2001 President’s Award: James W. Toothaker, DDS, MPH - Rebecca King, DDS, MPH, AAPHD (Blackwell Synergy, 2001)
The President’s Award is presented at the president’s discretion to a person who has provided special assistance to the president during her or his term. Today, I would like to present my President’s Award to a person who provided special assistance throughout my entire officer’s track.